Pengaruh Penyajian Laporan Keuangan Desa Dan Lingkungan Pengendalian Terhadap Pencegahan Fraud Dalam Pengelolaan Dana Desa Dengan Moralitas Individu Sebagai Variabel Moderasi Pada Kabupaten Asahan - Erika, Friti Sinta; Sari, Eka Nurmala; Sari, Maya (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This research is a research conducted to test and change the influence of Village Financial Report Presentation and Control Environment on Fraud Prevention in Village Fund Management with Individual Morality as a Moderating Variable in Asahan Regency, with an associative research approach, and data collection techniques by distributing questionnaires, the sample was 63 respondents and using path analysis techniques using the SEM PLS application. Based on the research results, it was concluded that the Presentation of Village Financial Reports has a relationship with a positive direction of influence on Fraud Prevention in village governments in Asahan Regency, the Control Environment has a relationship with a positive direction of influence on Fraud Prevention in village governments in Asahan Regency, Individual Morality moderates the influence of the Presentation of Village Financial Reports on Fraud Prevention in village governments in Asahan Regency, Individual Morality moderates the influence of the Control Environment on Fraud Prevention in village governments in Asahan Regency